Life beyond 5 Years after TAVI: Patients' Perceived Health Status and Long-Term Outcome after Transcatheter Aortic Valve Implantation. (1st October 2019) - Murray, Marie-Isabel K.; Hofmann, Eileen; De Rosa, Roberta; Mas-Peiro, Silvia; Seppelt, Philipp; Walther, Thomas; Zeiher, Andreas M.; Fichtlscherer, Stephan; Vasa-Nicotera, Mariuca
Abstract : Background . Transcatheter aortic valve implantation (TAVI) is currently recommended for patients with severe aortic stenosis at intermediate or high surgical risk. The decision process during TAVI evaluation includes a thorough benefit-risk assessment, and knowledge about long-term benefits and outcomes may improve patients' expectation management. Objective . To evaluate patients' perceived health status and self-reported long-term outcome more than 5 years after TAVI. Methods and Results . Demographic and procedure data were obtained from all patients treated with TAVI at our institution from 2006 to 2012. A cross-sectional survey was conducted on the patients alive, measuring health status, including the EQ-5D-5L questionnaire, and clinical outcomes. 103 patients (22.8%) were alive at a median follow-up period of 7 years (5.4–9.8). 99 (96%) of the 103 patients were included in the final analysis. The mean age at follow-up was 86.5 years ± 8.0 years, and 56.6% were female. Almost all patients (93.9%) described an improvement of their quality of life after receiving TAVI. At late follow-up, the mean utility index and EQ-VAS score were 0.80 ± 0.20 and 58.49 ± 11.49, respectively. Mobility was found to be the most frequently reported limitation (85.4%), while anxiety/depression was the least frequently reported limitation (19.8%). With respect to functional class, 64.7% were in New York Heart Association (NYHA) class III or IV, compared to 67.0% prior to TAVI (p = 0.51 ). Self-reported long-term outcomes revealed mainly low long-term complication rates. 74 total hospitalizations were reported after TAVI, and among those 43% for cardiovascular reasons. Within cardiovascular rehospitalizations, new pacemaker implantations were the most frequently reported (18.9%), followed by cardiac decompensation and coronary heart disease (15.6%). Conclusion . The majority of the patients described an improvement of health status after TAVI. More than five years after TAVI, the patients' perceived health status was satisfactory, and the incidence of clinical events and hospitalizations was very low.